RESPIRATORY RESPONSES IN A BRAZILIAN MILLIPEDE, PSEUDONANNOLENE-TRICOLOR, TO DECLINING OXYGEN PRESSURES - Penteado, CHS; Heblingberaldo, MJA (Univ Chicago Press, 1991)
Oxygen uptake and the influence of declining oxygen pressures (Po2's) were examined in a Brazilian spirostreptid millipede, Pseudonannolene tricolor. The data were obtained in a Warburg respirometer at 25-degrees-C from both male and female animals, sexually inactive, in the intermolt stage, and fasting for 24 h. In a sudden exposure to a decreased Po2 the millipedes regulated respiration down to at least 71 mmHg O2. From a Po2 of 35 mmHg O2 downward the animals started to show oxyconformity. When the millipedes were exposed to a stepwise declining Po2 the results indicated only conformation. After exposure to hypoxia, P. tricolor showed a pattern of underrepayment on return to normoxia, but larger millipedes accumulated more O2 debt than smaller ones.